2020
DOI: 10.3399/bjgp20x710477
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence during COVID-19: the GP role

Abstract: Threatened by COVID-19, the world has been on lockdown. Danger and death lay without; safety is to be found alone in the isolation of the home. The UK government's message was 'Stay at home … Do not meet others, even friends and family.' But within the walls of their own homes many women face an enemy more terrifying than COVID-19.The domestic abuse charity Refuge reported a 700% increase in calls in a single day. 1 The most recent findings are that '... demand has spiked again significantly -calls and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Almost half (43%) of the service providers highlighted and emphasised the growth in perpetrators use of control and coercion. This finding supports the range of national and international literature about the extent to which COVID‐19 has increased the range and intensity of abusive behaviour toward women and children (Gibson, 2020 ; Mazza et al, 2020 ; Pfitzner et al, 2020 ). Moreover, service providers indicated that some client groups were particularly vulnerable to increases in control and coercion.…”
Section: Key Findingssupporting
confidence: 80%
See 2 more Smart Citations
“…Almost half (43%) of the service providers highlighted and emphasised the growth in perpetrators use of control and coercion. This finding supports the range of national and international literature about the extent to which COVID‐19 has increased the range and intensity of abusive behaviour toward women and children (Gibson, 2020 ; Mazza et al, 2020 ; Pfitzner et al, 2020 ). Moreover, service providers indicated that some client groups were particularly vulnerable to increases in control and coercion.…”
Section: Key Findingssupporting
confidence: 80%
“…According to World Health Organization sources, the European Union has seen a rise of 60% in emergency calls from women experiencing domestic violence (Mahase, 2020 ). Based on data provided by DV organisation Refuge, in England, Gibson ( 2020 ) reported a weekly average increase in contact through their National Domestic Abuse Helpline and its Website of roughly 66% and tenfold increase in contact since the beginning of COVID‐19. Campbell ( 2020 ) argues the increasing prevalence of DFV was not reflected in official police reports due to the limited opportunities for victims to report during the pandemic when locked down with their abuser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Have other high risk patients, eg, patients with coronary heart disease, congestive heart failure [ 39 ] or diabetes mellitus [ 40 ], missed consultations with their GP, eg, in fear of getting infected with COVID-19? And have patients with social problems related to the lockdown, eg, family or partnership problems [ 41 ] and unemployment or workplace problems [ 42 , 43 ], consulted their GP more often than before the lockdown?…”
Section: Discussionmentioning
confidence: 99%
“…Identifying incidents directly related to home confinement questions its strict application among the most vulnerable [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%